The Changing Face of Athenian Government (403/2–168/7) - Osborne, Michael J. (Hyperboreus, 2017)
As is well known, decrees passed in the Athenian Assembly are classiﬁed as either probouleumatic (when based on a speciﬁc probouleuma proposed by a member of the Boule) or non-probouleumatic (when moved by a member of the Assembly in  response to an open probouleuma or as a replacement for a rejected probouleuma).  Recent studies have concluded ﬁrstly that from the beginning of the fourth century until ca. 285/260 there was a rough balance between probouleumatic and non-probouleumatic decrees, except in the brief oligarchic phase 322/1–319/8, when non-probouleumatic decrees were predominant, possibly as the result of some constitutional shift; and secondly that from ca. 285/260 onwards the vast majority of decrees (well over 80%) were probouleumatic, suggesting an inactive, if not apathetic, Assembly. A detailed examination of the available data indicates that the ﬁrst of these conclusions is overly generalised and inaccurate and that the date of the onset of ekklesiastic inactivity can be dated rather precisely to ca. 282/1. It is true that in the oligarchic phase 322/1–319/8 there was a predominance of non-probouleumatic decrees but this was not a novelty with possible constitutional implications but rather a continuation of the situation clearly evidenced in the so-called Lykourgan Period (337/6–323/2) in which some 80% of decrees were non-probouleumatic. Quite apart from this the evidence reveals that in the democratic period 403/2–338/7 probouleumatic decrees were signiﬁcantly more numerous than non-probouleumatic decrees, whereas in the brief democratic phase promoted by Demetrios Poliorketes (307–301) the reverse was the case.  (The evidence for the periods 318–308 and 300–287 is too slight for analysis.) From 282/1 onwards, once it had become clear that the revolt from Demetrios Poliorketes had been only partly successful in that Athens could not recover the Peiraieus and was essentially powerless, probouleumatic decrees, the majority of them mundane in nature, became predominant. The rationale for the predominance of non-probouleumatic decrees in the stated periods has nothing to do with constitutional change; rather it signiﬁes periods when the Assembly was dominated by one or a few strong individuals – Lykourgos and Demades in the 330s and 320s, Stratokles of Diomeia in the years 307–302. Restrictions on Boule membership and the greater prominence and publicity accorded to proposers of decrees in the Assembly – Stratokles moved at least three non-probouleumatic decrees in the year that he was a member of the Boule – made the link between powerful politicians and non-probouleumatic decrees inevitable.